Perceive Influence of the Use of Social Media on Information Seeking Behaviour of Undergraduates in Nigeria Universities - Mohammed Lawal Akanbi; Qudus Ajibola Bankole; Olaide Ayokunmi Olalekan; John Olajide Abiola (JINAV: Journal of Information and Visualization, 2022)
Social media has become prominent major source of information in our world today. Although the unique popularity of social media has infiltrated into undergraduates’ daily trajectories and become a vital part of their communication, yet surprisingly many undergraduates do not use social media for information relating to their academics little did they know that virtually all the information they need about their academics and practical can be gotten on social media. In order to address such research gap, the main objective of this research is to examine the perceive influence of the use of social media on information seeking behaviour of undergraduates in Nigeria universities. The study implored descriptive survey design, using Slovin’s formula and simple random sampling technique; three hundred ninety-eight (398) participants were conveniently sampled out of a population of 64,447 students. Findings revealed that undergraduates in make use of social media for information search often and it has been a reliable source of information for them. It is recommended that undergraduates should sharpen and improve their information literacy skills so as to overcome the challenges of unregulated nature of social media content. Social media has greatly impacted the information seeking behaviour of undergraduates in Nigeria universities